2012
DOI: 10.1007/s00403-012-1265-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of androgen and androgen receptor in skin-related disorders

Abstract: Androgen and androgen receptor (AR) may play important roles in several skin related diseases, such as androgenetic alopecia and acne vulgaris. Current treatments for these androgen/AR-involved diseases, which target the synthesis of androgens or prevent its binding to AR, can cause significant adverse side effects. Based on the recent studies using AR knockout mice, it has been suggested that AR and androgens play distinct roles in the skin pathogenesis, and AR seems to be a better target than androgens for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
120
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 116 publications
(155 reference statements)
0
120
0
2
Order By: Relevance
“…Finasteride inhibits 5a-reductase type 2 and 3 enzymes much more strongly than the type 1 enzyme 8,9 ; therefore, finasteride can affect several different human tissues, 4,5,8,10 such as the prostate, muscle, liver, kidney, brain, mammary gland, frontal cortex, skin, epidermis, pancreas, spleen, heart, testicle, stomach, dermis, small intestine, and adipose tissues. 8,9,11 Finasteride use has several adverse effects, including erectile dysfunction, loss of libido, and smaller ejaculatory volume. 5,10,12 A meta-analysis on the effects of 5a-reductase inhibitors found a significant pooled relative risk for sexual dysfunction in men with benign prostatic hyperplasia (2.56, 95% CI ¼ 1.48e4.42) but no significant increased risk in men with AGA (1.21, 95% CI ¼ 0.85e1.72).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finasteride inhibits 5a-reductase type 2 and 3 enzymes much more strongly than the type 1 enzyme 8,9 ; therefore, finasteride can affect several different human tissues, 4,5,8,10 such as the prostate, muscle, liver, kidney, brain, mammary gland, frontal cortex, skin, epidermis, pancreas, spleen, heart, testicle, stomach, dermis, small intestine, and adipose tissues. 8,9,11 Finasteride use has several adverse effects, including erectile dysfunction, loss of libido, and smaller ejaculatory volume. 5,10,12 A meta-analysis on the effects of 5a-reductase inhibitors found a significant pooled relative risk for sexual dysfunction in men with benign prostatic hyperplasia (2.56, 95% CI ¼ 1.48e4.42) but no significant increased risk in men with AGA (1.21, 95% CI ¼ 0.85e1.72).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, skin dryness was reported by users of finasteride against hirsutism 34 and by users of spironolactone, a drug used to treat hormonal acne by inhibiting the AR. 11 Androgens modulate the rate of cell turnover in the basal layer of the epidermis, the size and activity of the sebaceous glands, the quality of sebaceous secretions, the rate of hair growth, and stimulation of collagen production. 11,35 AR is present in fibroblasts and keratinocytes of human skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,11 Association with diseases proposed as being involved in the etiology of AGA, such as benign prostatic hyperplasia, prostate cancer, atherosclerosis, acne vulgaris, and testicular germ cell tumor, has been investigated in various studies, and it has been reported that AGA may be an early marker of these diseases. 9,10,[12][13][14] However, whether or not there is a correlation between AGA and urinary system stone disease, in whose etiology androgens have been shown to be involved, has not been investigated to date. In this study, we investigated whether patients with AGA were at risk in terms of urinary system stone disease.…”
Section: Introductionmentioning
confidence: 99%
“…It involves pathologically overproduction of serum, abnormal follicular keratinisation, formation of P. acnes biofilms and colonies, and finally the release of pro-inflammatory mediators to the skin. 1,2,3,4 Acne-prone individuals have larger sized sebaceous glands that are stimulated at the time of puberty. Several pathways and hormones beside androgens regulate the activity of sebocytes.…”
mentioning
confidence: 99%